Diagnostika a indikace operacni lécby nemocných s plicním karcinomem na I. klinice TRN 1. LF UK a VFN praha v letech 2004-2005 - Marel, M; Stránská, P; Mericka, O; Skácel, Z; Krejbich, F; Homolka, J; Zemanová, M (Casopis lekaru ceskych, 2006)
BACKGROUND: Results of the diagnostics and indications of surgical treatment of patients with lung carcinoma (BCA) at the First clinic in years 2004 to 2005 were evaluated in a retrospective study. METHODS AND RESULTS: The cohort of 209 patients with the male to female ratio of 2 to 1 included 63 % of current smokers, 22 % of former smokers and 15 % of non-smokers. BCA was diagnosed in significantly earlier age in smokers in comparison to former smokers or non-smokers. Men had smoked in average 107 000 of cigarettes more than women. In the family history we found one or more malignancies in 49 % of patients. In the personal history COPD was found in 42 % of patients. Patients with COPD had more frequently epidermoid type of cancer. In patients diagnosed at earlier stages of BCA (I to IIIA) COPD was present more frequently as an intercurrent disease in comparison with patients in higher stages. 34 % of patients had a history of alcohol abuse, the median age of alcoholic patients was 65 years, the median age of other patients was 70 years. In histologically verified tumours, the highest occurrence had the epidermoid type (29% of patients) and adenocarcinoma (27 %). 39 patients (18.6 % from the cohort) were surgically treated; from 128 patients with NSCLC 33 were surgically treated (25 % of NSCLC cohort). Among the causes of surgical treatment impossibility, the most frequent ones were COPD in the third to four stage, age over 80 years, polymorbidity and ill-being. CONCLUSIONS: Results of our study indicate that BCA is frequently diagnosed in already developed stage, numbers of surgically treated patients represent less than 20% of the total patients' number.
Keywords: nádory plic; Female; Aged; Lung Neoplasms; Smoking; Humans; ženské pohlaví; mužské pohlaví; senioři; lidé; kouření; lidé středního věku; Male; Middle Aged